Digital health revolution: perfect storm or perfect opportunity for pharmaceutical R&D?. Issue 6 (June 2016) - Hird, Nick; Ghosh, Samik; Kitano, Hiroaki
Highlights: Digital technologies are starting to cause major disruption in healthcare. They enable unprecedented ability for patient engagement and real-world monitoring. Pharma is ideally placed to drive implementation of digital technology in medicine. Digital medicine offers pharma new R&D opportunities to improve patient outcomes. Abstract : The convergence of technology and medicine has pushed healthcare to the brink of a major disruption that pharma has, until recently, been slow to recognize. Tech players have pioneered the emerging field of digital wellness and health, and pharma is ideally placed to use its expertise in drug development and embrace these technologies to create digital applications that address major medical needs. This review describes digital innovation from a pharma R&D perspective, outlining principal drivers, digital components, opportunities and challenges as well as a sustainable new business model predicated on empowered patients and achieving therapeutic outcomes. Teaser: Digital technologies are enabling closer patient engagement, offering pharma unprecedented R&D opportunities to create new therapeutic solutions and transition to a sustainable business model based on achieving patient outcomes.